2023
DOI: 10.1037/dev0001530
|View full text |Cite
|
Sign up to set email alerts
|

Infant crying predicts real-time fluctuations in maternal mental health in ecologically valid home settings.

Abstract: Exposure to infant crying is a well-established predictor of mothers' mental health. However, this association may reflect many potential mechanisms. Capturing dynamic fluctuations in mothers’ states simultaneously with caregiving experiences is necessary to identify the real-time processes influencing mental health. In this study, we leveraged ecological momentary assessments (EMAs) and infant-worn audio recorders to capture variability in mothers’ mental health symptoms and their exposure to infant crying ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…By utilizing these paradigms, researchers can test the ecological commitments (i.e., claims about theoretically relevant behavior or events outside of the laboratory settings) of their research, strengthening the understanding of psychological constructs and theories around early development (Dahl, 2017). For example, infant negative affect or reactivity is considered to be a relatively stable trait in early development (Rothbart et al., 2000), but infants’ moods and behaviors are likely to shift dynamically throughout the day (de Barbaro et al, 2023). Naturalistic research can test the ecological commitments made by these theories by capturing a rich variety of infants’ affective highs and lows across hours and days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By utilizing these paradigms, researchers can test the ecological commitments (i.e., claims about theoretically relevant behavior or events outside of the laboratory settings) of their research, strengthening the understanding of psychological constructs and theories around early development (Dahl, 2017). For example, infant negative affect or reactivity is considered to be a relatively stable trait in early development (Rothbart et al., 2000), but infants’ moods and behaviors are likely to shift dynamically throughout the day (de Barbaro et al, 2023). Naturalistic research can test the ecological commitments made by these theories by capturing a rich variety of infants’ affective highs and lows across hours and days.…”
Section: Discussionmentioning
confidence: 99%
“…This is a possibility with our research protocol, given that multiple cries were collected per dyad. Extended recordings (24 h+) from multimodal home sensor protocols can further facilitate this research, as many additional spontaneous crying events can be collected from each participant across hours and days (Buhler‐Wassmann & Hibel, 2021; de Barbaro et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Rome IV criteria, infantile colic is diagnosed when the caregiver reports a baby crying or fussing for three or more hours per day for three or more days within 7 days during a telephone or face‐to‐face screening interview 3 . The prevalence of infant colic varies significantly worldwide 4 …”
Section: Introductionmentioning
confidence: 99%
“…3 The prevalence of infant colic varies significantly worldwide. 4 Infantile colic can be challenging to treat due to its multifactorial and partially unknown pathophysiology. 3 Research has shown that behavioural and biological factors can contribute to the development of infant colic.…”
mentioning
confidence: 99%